Variation in the toxicity of sediment-associated substituted phenylamine antioxidants to an epibenthic (Hyalella azteca) and endobenthic (Tubifex tubifex) invertebrate. (August 2017) - Prosser, R.S.; Bartlett, A.J.; Milani, D.; Holman, E.A.M.; Ikert, H.; Schissler, D.; Toito, J.; Parrott, J.L.; Gillis, P.L.; Balakrishnan, V.K.
Abstract: Substituted phenylamine antioxidants (SPAs) are produced in relatively high volumes and used in a range of applications (e.g., rubber, polyurethane); however, little is known about their toxicity to aquatic biota. Therefore, current study examined the effects of chronic exposure (28 d) to four sediment-associated SPAs on epibenthic ( Hyalella azteca ) and endobenthic ( Tubifex tubifex ) organisms. In addition, acute (96-h), water-only exposures were conducted with H. azteca . Mortality, growth and biomass production were assessed in juvenile H. azteca exposed to diphenylamine (DPA), N -phenyl-1-napthylamine (PNA), N -(1, 3-dimethylbutyl)-N'-phenyl-1, 4-phenylenediamine (DPPDA), or 4, 4'-methylene-bis[ N - sec -butylaniline] (MBA). Mortality of adult T. tubifex and reproduction were assessed following exposure to the four SPAs. The 96-h LC50s for juvenile H. azteca were 1443, 109, 250, and >22 μg/L and 28-d LC50s were 22, 99, 135, and >403 μg/g dry weight (dw) for DPA, PNA, DPPDA, and MBA, respectively. Reproductive endpoints for T. tubifex (EC50s for production of juveniles > 500 μm: 15, 9, 4, 3.6 μg/g dw, for DPA, PNA, DPPDA, and MBA, respectively) were an order of magnitude more sensitive than endpoints for juvenile H. azteca and mortality of adult worms. The variation in toxicity across the four SPAs was likely related to the bioavailability of the sediment-associated chemicals, which was determined by the chemical properties of the SPAs (e.g., solubility in water, Koc). The variation in the sensitivity between the two species was likely due to differences in the magnitude of exposure, which is a function of the life histories of the epibenthic amphipod and the endobenthic worm. The data generated from this study will support effect characterization for ecological risk assessment. Highlights: 28-d LC50s H. azteca exposed to sediment-associated SPAs ranged 22 – > 403 μg/g dw. 28-d EC50s T. tubifex exposed to sediment-associated SPAs ranged 3.6–15 μg/g dw. Variation in toxicity between SPAs corresponded with Koc. Variation in toxicity between species due to variation in pathway of exposure.